NILAI-NILAI KEHIDUPAN DALAM NOVEL LAKI-LAKI DARI SELATAN KARYA TAN TJIN SIONG - Putra, Muhammad Ananda; Syam, Christanto; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to obtain an overview of the values of life in the novel Male From The South by Tan Tjin Siong. The study uses descriptive and qualitative methods. The approach used is the sociological approach to literature. Sources of data in this study relate to the value of education and moral values related to individuals, moral values associated with society, and moral values related to divinity that are reflected in words, phrases, and sentences in the novel Male From The South by Tan Tjin Siong. Based on the results of data research on the novel Male From The South by Tan Tjin Siong, it can be concluded that there is a value of education. The form of its educational value is Honest. Moral values related to individuals. His form is strong desire, and humble. Moral values related to the community, the form of moral values are faithful, a sense of family, obedient to parents, and deliberation. Moral values related to God. The form of its moral value is praying, believing soul mates in the hands of God, and surrender to God.Â Keywords: life values, novels